Ecology of vertical life in harsh environments: The case of mycorrhizal symbiosis with secular cliff climbing trees (Juniperus phoenicea L.). (November 2016) - Sanguin, Hervé; Mathaux, Coralie; Guibal, Frédéric; Prin, Yves; Mandin, Jean-Paul; Gauquelin, Thierry; Duponnois, Robin
Abstract: The Phoenician juniper tree ( Juniperus phoenicea L.) is emblematic of Mediterranean ecosystems. Secular trees from a relict population are present in the cliffs of the Ardèche gorges (protected natural reserve). This population shows a remarkable adaptability to major physical, nutrient and water availability constraints. The basis of its adaptation to hostile environmental conditions is poorly understood. The aim of the study is to decipher the diversity and structure of the Phoenician juniper mycorrhizal community in order to highlight mycorrhizal characteristics related to the particular ecology of this relict population. We hypothesized that a long-term co-evolution between arbuscular mycorrhizal (AM) fungi and the plant partner, emphasized by a geographic isolation, may have selected a specific mycorrhizal community playing a key role in J. phoenicea adaptation. 454-sequencing of AM fungal community from Phoenician juniper secular trees revealed a complex community, notably composed of Rhizophagus and poorly-affiliated Glomeraceae clades. The AM fungal community characterized was mainly related to those found in arid and semi-arid habitats, strengthening the ecological specificity of the Phoenician juniper AM fungal communities to harsh environmental conditions. Highlights: Mycorrhiza associated with a relict Phoenician juniper population facing major environmental constraints was explored. Rhizophagus and poorly-affiliated Glomeraceae clades are predominant. Phoenician juniper mycorrhizal community structure is similar to those inhabiting arid and semi-arid habitats.